Analysis of the Validity of Oral Agreements According to Civil Law in Indonesia - Deanna Fitri Roshandi (Law and Justice research journal, 2025)
In everyday life, the practice of making agreements often occurs informally and without written documentation, particularly in casual social interactions and economic activities. This raises important legal questions regarding whether verbal agreements hold valid legal force. The purpose of this study is to examine the legal status of verbal agreements under Indonesian civil law, particularly in relation to the requirements for the validity of an agreement as outlined in Article 1320 of the Civil Code (KUHPerdata). The study employs a normative juridical approach, focusing on legal provisions and legal doctrines to explore the issue. According to the findings, while verbal agreements are legally binding, they must still meet the requirements stipulated in Article 1320 of the Civil Code. These requirements include mutual consent, the capability of the parties involved, a lawful object, and a legal cause. Despite the lack of a written record, verbal agreements can still be considered valid as long as these criteria are met. However, a significant challenge arises when disputes occur, as proving the existence and terms of a verbal agreement can be difficult without written evidence. This is where the importance of written agreements comes into play, as they provide stronger legal protection in case of legal conflicts. The study also highlights that although Indonesian civil law recognizes verbal agreements, it strongly encourages parties to formalize agreements in writing to avoid ambiguity and ensure legal certainty. In conclusion, while verbal agreements are valid under the law, the need for written documentation is crucial for protecting the interests of the parties involved and providing clear evidence in the event of a legal dispute.